STUDIES ON RECENT DEATH CASES OF TUBERCULOSIS - OKUBO, Itsuko; HIGUCHI, Haruyuki; TAKAHASHI, Yoshio; KATSUI, Yoshikazu; UMAOKA, Shin; UCHIDA, Fumiya; YOSHINAGA, Nobutaka; HATA, Tadahiko; KASHIWAGI, Hideo; FUJII, Hideko (Japanese Journal of National Medical Services, 1990)
Forty-two death cases of tuberculosis (120 of 350 inpatients with tuberculosis) happened in our hospital during the 5-year period from 1984 through 1989. The age of the time of death was over 70 years old in 66.7 per cent of the total death cases. Twenty-three cases (54.8%) received initial chemtoherapy and 8 cases (19.0%) received repeat-chemo-therapy. Four cases (9.5%) were persisters. Seven cases with sequelae of tuberculosis (16.7%) received no chemotherapy. Eight cases (19.4%) had positive M. tb. in sputum and 5 cases (11.9%) had positive atypical mycobacterium in terminal stage. As to their cause of death, death from respiratory failure occurred in 12 cases (28.6%), death from pneumonia occurred in 7 cases (16.7%), death from cancer occurred in 9 cases (21.4%) and death from tuberculosis occurred in 3 cases (7.1%). Death of respiratory failure and hemoptysis from tuberculosis and tuberculosis death were 30.9 per cent of total death cases. Poor prognostic factors were found in respiratoy failure (33.3% of total cases), airway infection (16.7%) bedridden patients (14.3%) and low nutrients (23.8%).